The lost daughter : A memoir - Williams, Mary (New York : Blue Rider Press, 2013)
The adopted daughter of Jane Fonda describes her youth in 1970s Oakland, California, her daunting prospects in the face of her dysfunctional biological family, and the ways in which a structured home life enabled her eventual reconnection with her biological family.
"A memoir"--Jacket.
99967
Keywords: Williams, Mary, -- 1967- -- Childhood and youth; Fonda, Jane -- 1937-; Black Panther Party -- History; African Americans -- California -- Oakland; African Americans -- California -- Oakland -- Social conditions -- 20th century; Adoptees -- California; Mothers and daughters -- California; Oakland (Calif.) -- Social conditions -- 20th century